Cardiac MRI in evaluation and management of pediatric pericarditis. (September 2018) - Baskar, Shankar; Betancor, Jorge; Patel, Kunal; El Yaman, Malek; Cremer, Paul C.; Zeft, Andrew S.; Klein, Allan L.
Abstract: Background: Evaluation of pediatric pericarditis depends on the physical examination, electrocardiography and echocardiography. However, a multimodality imaging approach which includes cardiac magnetic resonance imaging (MRI) has been adopted in the adult population. The use of such an approach in the pediatric population has not been studied well. Objective: The present study was intended to describe a single institution's experience with the use of cardiac MRI in the evaluation of pericarditis in the pediatric population. Study Design: A retrospective review of patients who had a cardiac MRI before the age of 21 years, between 2005 and 2014, to evaluate for pericardial pathology including pericarditis, constrictive pericarditis, recurrent pericarditis and pericardial effusion was performed. Patients were excluded if the cardiac MRI was done for evaluation of pathologies other than those related to the pericardium. Patients with predominant myocarditis were also excluded. The cardiac MRI and the echocardiograms were reviewed by a single blinded investigator. Results: Twenty-one patients satisfied the inclusion criteria. The study population were predominantly male (81%) older adolescents (mean age: 17 ± 3 years). The major indications for cardiac MRI included evaluation of myocardial involvement in acute pericarditis, modulation of therapy in recurrent pericarditis and confirmation of constriction. Cardiac MRI was comparable to echocardiogram in detecting constrictive physiology and was useful in determining the presence of active pericardial inflammation. Systemic inflammatory diseases demonstrated higher values on quantification of late gadolinium enhancement. Conclusion: We have reported on a relatively large series of pediatric patients with pericarditis evaluated by cardiac MRI. Cardiac MRI may be a useful adjunct to conventional imaging in selected pediatric patients with pericarditis. Highlights: Cardiac MRI can be useful in the evaluation of pediatric pericarditis. Cardiac MRI frequently demonstrated pericardial late gadolinium enhancement indicating active pericardial inflammation in selected patients, who had a normal echocardiogram. Cardiac MRI is comparable to echocardiogram in demonstrating constrictive physiology. There is a higher degree of late gadolinium enhancement in patients with systemic disease and recurrent pericarditis.